2010
DOI: 10.1016/j.transproceed.2010.05.112
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Transplantation Prevents Morphologic and Ultrastructural Changes in Pulmonary Parenchyma of Alloxan-Induced Diabetic Rats

Abstract: We conclude that PT can control morphologic and ultrastructural changes in pulmonary parenchyma, suggesting a promising perspective for preventing other chronic diabetic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…Assessment of the morphological characteristics of lung tissue showed that diabetic animals exhibited different pulmonary structure when compared to healthy rats. Increase in bronchovascular wall thickening, presence of inflammatory infiltrate and pulmonary edema were some of the anatomopathological findings, corroborating other studies (Goldman, 2003;Eren et al, 2010;Spadella et al, 2010;Hagiwara et al, 2011). These investigations also demonstrated morphofunctional alterations in the lung tissue of diabetic rats.…”
Section: Discussionsupporting
confidence: 90%
“…Assessment of the morphological characteristics of lung tissue showed that diabetic animals exhibited different pulmonary structure when compared to healthy rats. Increase in bronchovascular wall thickening, presence of inflammatory infiltrate and pulmonary edema were some of the anatomopathological findings, corroborating other studies (Goldman, 2003;Eren et al, 2010;Spadella et al, 2010;Hagiwara et al, 2011). These investigations also demonstrated morphofunctional alterations in the lung tissue of diabetic rats.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies conducted in our laboratory have previously shown that PT is not only able to restore the endocrine balance in ALX-induced diabetic rats but can also prevent or stabilize the progression of diabetic lesions in the kidneys, eyes, nerves and lungs of these animals [45][46][47][48]. These findings have been confirmed by others in humans [4][5][6][7].…”
Section: Discussionsupporting
confidence: 68%